2022
DOI: 10.1039/d1ra07983b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and quantum chemical studies on the corrosion inhibition of 1037 carbon steel by different types of surfactants

Abstract: In this work, three different types of surfactants DTAC, C12H25N (CH3)3Cl−, TX-100, C34H62O11 for x = 10) and AOT-100, C20H37O7NaS) with corrosion restraint were utilized as corrosion inhibitors for 1037 CS in 0.5 M HCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The smaller arc for NF50 provided a low R ct , which predicted a rapid charge-transfer kinetics (Table S2). 34 Although, metal oxides are inherent insulators, in situ formed metal oxide or oxyhydroxide overlayer on the precatalyst often shows better charge transfer compared to pristine material due to formation of heterojunction. 35 Modification of the electronic property in the interfacial region of this heterojunction facilitates the charge conduction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller arc for NF50 provided a low R ct , which predicted a rapid charge-transfer kinetics (Table S2). 34 Although, metal oxides are inherent insulators, in situ formed metal oxide or oxyhydroxide overlayer on the precatalyst often shows better charge transfer compared to pristine material due to formation of heterojunction. 35 Modification of the electronic property in the interfacial region of this heterojunction facilitates the charge conduction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The higher ECSA value may result in better adsorption of an analyte at the electrode−electrolyte interface, which may also enhance the local dielectric constant with the wide thickness of the electrical double layer. 34 The trend of ECSA can also be correlated with the charge transfer resistance (R ct ) determined from the electrochemical impedance spectroscopy (EIS) study with the electrodes. EIS was performed at a constant applied potential of 1.64 V (vs RHE).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of SS/Ti(N,O) coatings, the slopes were quite similar, such that it may be concluded that the hydrogen evolution and metal dissolution were almost in equilibrium [61]. For the ALD-coated samples, except for SS/Ti(N,O)/HfO 2 -110c, the anodic slope became higher than the cathodic slope, indicating an inhibition action of the oxides by simply blocking the metal from interaction with the acidic and oxidising environment [62][63][64]. Considering the Tafel plots (Figure 17b-d), one can see that both the uncoated and Ti(N,O)-coated SS showed a local disruption of the passive layer, evidenced by the breakdown potential (Eb), giving rise to a sharp increase in the ion current density, indicating that local corrosion processes were activated.…”
Section: Electrochemical Evaluation-tafel Plotsmentioning
confidence: 93%
“… Naidu and Joseph (2022) state that corrosion in reinforced concrete happens when an aggressive substance, such as chloride, diffuses into the reinforcement. Although there are several ways to prevent corrosion, using inhibitors is still the most popular method ( Saha et al, 2015b ; Saha et al, 2015a ; Saha et al, 2016 ; Saha et al, 2019 ; Saha et al, 2021 ; Fouda et al, 2022 ; Saha et al, 2022 ; Wang et al, 2022 ; Bijapur et al, 2023 ; Li et al, 2023 ). Prior research has extensively examined the application of synthetic organic compounds with heteroatoms, heterocyclic rings, and aromatic rings to reduce corrosion aggression on steel.…”
Section: Introductionmentioning
confidence: 99%